2022
DOI: 10.15212/amm-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-carotene on glucose metabolism dysfunction in humans and type 2 diabetic rats

Abstract: Background Type 2 diabetes mellitus (T2DM) is a common chronic disease that is strongly associated with cardiovascular risk. Long-term high blood glucose levels may induce cardiomyocyte apoptosis, cardiac dysfunction and suppress fetal cardiomyocyte proliferation. Recent epidemiological studies have shown a link between antioxidant carotenoids and T2DM, but a comprehensive longitudinal study of this association has not yet been conducted. Methods We included participants with biological measurements for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A systematic review of dietary and nutritional contributors to the development of gout was presented by Zhang et al They found that energy-type nutritional overloads diets such as high-sugar and high-fat diets can induce hyperuricemia and inflammation, whereas adequate intake of essential nutrients is highly beneficial in gout [ 11 ]. Vitamins like vitamin A [ 39 ], vitamin D [ 40 ], and vitamin C [ 41 , 42 ] exhibit helpful anti-oxidative stress and anti-inflammatory effects with effective reduction of serum uric acid levels. Increasing the consumption of vitamins, fiber as well as unsaturated fatty acids, and supplementing with the right amount of minerals together with premium protein, can improve gout symptoms by promoting systemic metabolism [ 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of dietary and nutritional contributors to the development of gout was presented by Zhang et al They found that energy-type nutritional overloads diets such as high-sugar and high-fat diets can induce hyperuricemia and inflammation, whereas adequate intake of essential nutrients is highly beneficial in gout [ 11 ]. Vitamins like vitamin A [ 39 ], vitamin D [ 40 ], and vitamin C [ 41 , 42 ] exhibit helpful anti-oxidative stress and anti-inflammatory effects with effective reduction of serum uric acid levels. Increasing the consumption of vitamins, fiber as well as unsaturated fatty acids, and supplementing with the right amount of minerals together with premium protein, can improve gout symptoms by promoting systemic metabolism [ 28 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…By reason of Wnt/β‐catenin signaling associated with lung and brain metastasis in patients with TNBC, blocking Wnt/β‐catenin pathway can inhibit breast metastasis (Krishnamurthy & Kurzrock, 2018). Moreover, KMO has been confirmed to bind to β‐catenin and the glycogen synthase kinase 3β (GSK3β) complex to reduce GSK3β kinase activity, leading to a decrease in phosphorylated β‐catenin that is susceptible to ubiquitination and degradation, thereby affecting the stability of β‐catenin (Wu et al, 2022). In general, the nonenzymatic function of KMO can promote the stability of β‐catenin and the expression of pluripotent genes, which indicate that KMO plays an important role to suppress the GSK3β kinase activity against β‐catenin (T. T. Huang, Tseng et al, 2020).…”
Section: The Involvement Of Kmo In Diversity Diseasesmentioning
confidence: 99%
“…Diabetes mellitus is a lifelong disorder that demands dietary restrictions and pharmacotherapy 1,2 and brings infinite discomfort and pain to patients. The prominent problems of diabetes mellitus are reflected in the following aspects: the high cost of diabetic care and management aggravates economic burden; 3 this trend continues to spread around the world, 4 and public health and life are confronted with serious threats.…”
Section: Introductionmentioning
confidence: 99%